ИССЛЕДОВАНИЯ КОНВЕКТИВНОГО ТЕПЛООБМЕНА ПРИ ЭЛЕКТРОГИДРАВЛИЧЕСКОМ ВОЗДЕЙСТВИИ - Нусупбеков, Б.Р. (Изд-во КарГУ., 2009)
Мақалада соңғы кезде кең ауқым алып келе жатқан электрогидравликалық эффектіні қолдану жолдары қарастырылған. Сұйықтардың əр түрлі жылдамдықтары кезіндегі температура- лардың таралуы мен жылу беру коэффициенттерінің артуы қарастырылған. Сонымен қатар жылуалмастырғыштардағы пайда болатын қақтарды тазалау жолдары көрсетілген. In the given work has been devoted to research of influence of electrohydraulic effect on heat exchange of a lamellar surface. Experimental electrohydraulic installation is developed and collected. As shows an expert, a physical basis of heat exchange by electrohydraulic influence is the turbulence of a boundary layer on a surface of heat exchange. At equal speeds and constant temperature of a stream average factors of heat exchange were defined at known density of a thermal stream. At all values of frequency of the recharge the general law of influence of number of Reynolds on local factor of heat exchange is observed. The minimal value of energy at which destruction of adjournment of the investigated brass pipe begins, is equal nearby 45 Joule. From the received results the length defining area of destruction follows, that, can make, at least, some calibres of diameter of a pipe.
Keywords: конвективный теплообмен; электрогидравлическая воздействия; исследования